Financial Risks in Supply Chain Management: Causes and Consequences - Sinaga, Obsatar; Wahdiaman, Wahdiaman; Rumaisa, Fitrah; Zainudin, Zalina (ExcelingTech, 2019)
The principal purpose of the current study is to explore the nexus between supply chain financial risk, supply chain operational performance and supply chain management. To achieve the objective of the current study we have proposed two direct and one indirect hypothesis. To achieve the objective of the current study, we have employed the structural equation modeling and used the statistical package of smart PLS-3. The data by mean of an adapted survey instrument in the form of questionnaire is collected from the operation and finance managers of manufacturing firms. The results of the current study are providing support to the hypothesized results as supply chain financial risk appear in significant relationship with firm supply performance. Meanwhile the supply chain operational risk is in significant relationship with supply chain management and also significantly moderate the relationship between supply chain financial risk and supply chain management. The current study which in author knowledge is among few pioneering studies on this issue, will be helpful for financial experts, operation managers, academicians, researchers and other policy makers in formulating policies.